Effect of Developed Captioned-Video in English on the Performance of Hearing-Impaired Students in Upper Basic School, Kaduna. - Fakomogbon, Michael Ayodele; Obielodan, Omotayo Olabo; Amosa, Abdulganiyu Alasela; Amoka, Grace Oisa (NIU Journal of Humanities, 2017)
This study examined the effect of a developed Captioned-video in English on the performance of hearing-impaired students in upper basic school, Kaduna, Nigeria. The study combined qualitative and quantitative research methods, involving one group pretest-posttest experimental research design. Three research questions and three hypotheses were raised and formulated respectively. The population for this study comprised all hearing-impaired students in Kaduna State, Nigeria. The target population were all JSS 1 upper basic students in Kaduna State Special Education School (KASSES). Twenty-nine (29) of these students were selected as the sample for this study. Three research instruments were used in this study. They include: Captioned-video to Teach English Language (CVTEL), Student’s Performance Test in English Language (SPTEL), and Student’s Attitudinal Questionnaire (SAQ). A total of fourteen (14) experts were engaged in validating the three research instruments to ensure suitability and content appropriateness. The experimental group was initially pre-tested using Student’s Performance Test in English Language (SPTEL), then exposed to the Captioned-video and a post-test after. An attitudinal questionnaire was given to the students to elicit responses on their reaction to the Captioned-video. All instruments were field validated.  The findings revealed amongst others that; significant difference existed between the performances of hearing-impaired students taught English language before and after exposure to the Captioned-video. The students performed better in the post-test than in the pre-test and no significant difference existed in the performance of male and female hearing-impaired students that were exposed to the Captioned-video. The study concluded that the Captioned-video improved hearing-impaired students’ performance in English language, irrespective of gender and the students also expressed positive attitude to the use of the Captioned-video. It was therefore recommended that teachers develop Captioned-videos to meet educational standards and maximize their use for educating hearing-impaired students. Keywords : Captioned-video, Hearing-Impaired, Performance, Attitude, Gender.